2018
DOI: 10.3747/co.25.3888
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–Lymphocyte Ratio Predicts Response to Chemotherapy in Triple-Negative Breast Cancer

Abstract: BackgroundThe neutrophil-lymphocyte ratio (nlr) has been reported to correlate with patient outcome in several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 47 publications
4
50
1
Order By: Relevance
“…Salim et al also reported that the NLR is an independent prognostic factor in patients with recurrent or metastatic HNSCC . On the other hand, previous studies suggested that the NLR predicts chemotherapy outcomes in patients with various types of cancer . Although the clinical benefit (SD + PR) were observed in some of the patients with pretreatment NLR of ≥5.0 as well as in patients with pretreatment NLR of <5.0, pretreatment NLR ≥5.0 is associated with worse survival in patients undergoing nivolumab monotherapy in this study.…”
Section: Discussionmentioning
confidence: 42%
“…Salim et al also reported that the NLR is an independent prognostic factor in patients with recurrent or metastatic HNSCC . On the other hand, previous studies suggested that the NLR predicts chemotherapy outcomes in patients with various types of cancer . Although the clinical benefit (SD + PR) were observed in some of the patients with pretreatment NLR of ≥5.0 as well as in patients with pretreatment NLR of <5.0, pretreatment NLR ≥5.0 is associated with worse survival in patients undergoing nivolumab monotherapy in this study.…”
Section: Discussionmentioning
confidence: 42%
“…According to our scatter plot, ALC appeared to be useful in distinguishing patients with a favorable status, whereas NLR appeared to be useful in distinguishing those with an unfavorable status. Most studies prior to the present one determined their cutoff values on the basis of receiver-operating char- acteristic curves, the median value in their own cohorts, or cutoff values reported elsewhere [15,19,20]. As a result, cutoff values of 2.0-3.3 were commonly used for NLR, despite being almost average [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…(1) Patients Receiving Neo-Adjuvant Therapy Ten studies reported data on NLR as a predictive or prognostic factor in patients receiving neo-adjuvant therapy [22][23][24][25][26][27][28][29][30][31]. Among these studies, eight included patients with all molecular subtypes [22][23][24][25][26][27][28][29], one included only patients with triple negative BC (TNBC) [31] and the last one included only patients with hormone receptor-positive/HER2-negative BC [30]. The NLR cut-off for the statistical analyses was between 1.7 and 3.33, and was computed by a receiver operating characteristic (ROC) curve analysis in all studies.…”
Section: In Early Bcmentioning
confidence: 99%
“…The number of enrolled patients ranged from 78 to 373. Five studies reported data on Asian populations [23,25,28,30,31]. In nine articles, the neo-adjuvant therapy protocols were described, and were based on anthracycline and/or taxane [23][24][25][26][27][28][29][30][31].…”
Section: In Early Bcmentioning
confidence: 99%